The use of Cause and Effect Diagram (Fishbone) and its impact on Personal Quality Management: Case Study in a classroom during the pandemic of COVID – 19 - Deliou, Cleopatra; Malagkoniari, Maria (International Conference on Business and Economics - Hellenic Open University, 2023)
Personal quality and total quality management (TQM) are key success factors for organizational performance. The combination of individual and team quality management actions leads to motivated people in the workplace and can create high quality processes, relationships and outputs. The Cause and Effect Diagram (Fishbone) is one of the seven most known quality tools and it provides a systematic way of looking at effects and the causes that create or contribute to those effects. It helps an organization to identify, analyze and improve quality issues. This study examines the use of the Cause and Effect Diagram (Fishbone) quality tool in a classroom during the pandemic of COVID – 19. After the use of the tool by the class participants on personal and team level, students were also asked to assess its impact and provide feedback over the connection of this tool application to personal quality development. The researchers concluded that on a team basis, the Cause and Effect Diagram helped the team members visually diagram the problems and allowed them to truly diagnose the problem, to separate a problem's content from its history, and facilitated team consensus around its causes. Finally, it is well – known that by team action are cultivated skills such as cooperation, team – thinking, determination, persuasion, creativity, inspiration, fast problem solving, synergy, immediate decision making and direct communication. EL Classification: Μ19 Keywords: Total Quality Management, Personal Quality, Cause and Effect Diagram, Personal and Team Projects